1989
DOI: 10.1007/bf00612995
|View full text |Cite
|
Sign up to set email alerts
|

Spectral sensitivity in jumping spiders (Araneae, Salticidae)

Abstract: 1. We report here a psychophysical technique for studying the spectral sensitivity of jumping spiders (family Salticidae), based on a newly discovered oculomotor reflex. 2. Our results, obtained from Maevia inclemens (Salticidae), are compatible with electrophysiological findings of retinal cells maximally sensitive in the green and ultraviolet regions of the spectrum. 3. Sensitivity to longer wavelengths (greater than 650 nm) has been controversial. In our study jumping spiders are shown to have a broad spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…It is also known that a few species of salticids can distinguish colours (Homann, 1928;Nakamura and Yamashita, 2000) and have UV photoreceptors in their eyes (DeVoe, 1975;Yamashita and Tateda, 1976;Blest et al, 1981;Peaslee and Wilson, 1989). Electrophysiological experiments, including experiments based on intracellular recordings from individual photoreceptor cells in the principal-eye retina, have revealed that four species of salticids have UV-sensitive photoreceptor cells in the retina, with peak sensitivity in the range of 330-380nm: Phidippus regius (DeVoe, 1975), Menemerus fulvus (formerly confuses) (Yamashita and Tateda, 1976), Plexippus validus (Blest et al, 1981) and Maevia inclemens (Peaslee and Wilson, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that a few species of salticids can distinguish colours (Homann, 1928;Nakamura and Yamashita, 2000) and have UV photoreceptors in their eyes (DeVoe, 1975;Yamashita and Tateda, 1976;Blest et al, 1981;Peaslee and Wilson, 1989). Electrophysiological experiments, including experiments based on intracellular recordings from individual photoreceptor cells in the principal-eye retina, have revealed that four species of salticids have UV-sensitive photoreceptor cells in the retina, with peak sensitivity in the range of 330-380nm: Phidippus regius (DeVoe, 1975), Menemerus fulvus (formerly confuses) (Yamashita and Tateda, 1976), Plexippus validus (Blest et al, 1981) and Maevia inclemens (Peaslee and Wilson, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological experiments, including experiments based on intracellular recordings from individual photoreceptor cells in the principal-eye retina, have revealed that four species of salticids have UV-sensitive photoreceptor cells in the retina, with peak sensitivity in the range of 330-380nm: Phidippus regius (DeVoe, 1975), Menemerus fulvus (formerly confuses) (Yamashita and Tateda, 1976), Plexippus validus (Blest et al, 1981) and Maevia inclemens (Peaslee and Wilson, 1989). The existence of opsin gene Rh3 also suggests the likelihood of UV sensitivity in Hasarius adansoni and Plexippus paykulli (Koyanagi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Up to four different types of photoreceptors were found in salticids (Land, 1969;De Voe, 1975;Yamashita and Tateda, 1976;Blest et al, 1981), leading to a broad spectral sensitivity from 330nm up to 700nm (Peaslee and Wilson, 1989). Colour vision abilities were investigated in simple behavioural experiments where coloured stripes could be discriminated (Kästner, 1950), and in a more elaborate heat-avoidance learning test the animals could discriminate the colours blue, green, yellow and red (Nakamura and Yamashita, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Their anterior median eyes are adapted for both high spatial resolution (Eakin and Brandenburger, 1971) and for color vision (DeVoe, 1975;Land, 1969a;Land, 1969b;Land, 1985;Peaslee and Wilson, 1989). These eyes, in combination with three pairs of motion-detecting eyes, result in the most highly developed visual system in spiders (Land, 1985).…”
Section: Introductionmentioning
confidence: 99%